(untitled) (Hematology Meeting Reports, 2009)
During the past ten years, major advances in the treatment have improved the outlook in myeloma. The antitumor activity of thalidomide, bortezomib and lenalidomide has been discovered. In elderly patients, the combination of these new drugs with conventional chemotherapy has been reported to induce a high response rate and to improve overall survival. In young patients, these new drugs have been evaluated to improve the outcome of high dose therapy supported with autologous transplantation. This abstract will focus on the impact of these new drugs in the transplantation setting: 1) during induction therapy, 2) combined with the high dose regimen, and 3) used as maintenance therapy post transplantation.